Ekspresi Warna Ecoprint Daun Jati (Tectona grandis) Pada Katun Primissima dengan Mordan Tawas, Tunjung dan Kapur - UMI KULSUM NUR QOMARIAH; Vina Ainul Bashiroh; Miftachul Chusna (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The availability of abundant natural materials in Indonesia strongly supports the development of textile products, one of which is natural coloring which can be obtained from natural materials such as teak leaves. Teak leaves contain natural anthocyanin pigments that can be used as environmentally friendly textile dyes. Transfer of pigment to the fabric can be done using the ecoprint technique, which requires a mordant for the color binding process to prevent it from being easily separated from the fabric. The purpose of the research to determine the color expression of teak leaf ecoprints with mordant alum, tunjung and calcium dioxide on primissima cotton fabric and to determine the effect of variations in boiling time during mordanting on the color expression of teak leaf ecoprints. The research was carried out experimentally using the ecoprint steam technique to transfer colors and motifs into the fabric. This study used three types of mordant substances, there are: alum, tunjung and calcium dioxide with each concentration of 50g/l with variations in boiling time for mordanting: 20 minutes, 40 minutes and 60 minutes and three replications in each treatment. The ecoprint technique applied is steaming for 80 minutes. The results showed that the color expression produced by the alum mordant was dominated by yellow, the color produced from the tunjung mordant was dominated by black and the dye produced by quicklime was dominated by brown. The natural motif of teak leaves can be printed well on primissima cotton. The variation of boiling time during mordanting in this study did not produce differences in color expression because there was no variation in the concentration of the mordant substance.